DIFFERENCES IN SOCIAL STATUS THAT AFFECT RELATIONSHIPS IN JANE AUSTEN’S PERSUASION - Polii, Tania Oktavina; Samola, Nurmin; Andries, Fivy A. (JoTELL : Journal of Teaching English, Linguistics, and Literature, 2024)
The aim of this research is to reveal differences in views of social status that influence relationships in the Jane Austen Persuasion. This research used qualitative research, where the research technique stems from an inductive thinking pattern, which is based on objective, participatory observation of a social symptom phenomenon. Data was taken from the novel using a sociological approach. In addition, researcher used analysis of forms of social status by Ralph Linton to reveal differences in views of social status in the novel Persuasion. From this research it can be concluded that there are three forms of social status in the novel Persuasion. Social status is also a term that describes a person’s position in a society or social group, which is usually called a person’s position, and also social status is a description of the socioeconomic position of a person or society. The forms of social status are ascribed status, achieved status, and assigned status